Counselor-Perceived Teacher Actions Needed to Carry out Educational and Vocational Guidance in Secondary Schools in Spain - Falcón-Linares, Carolina; Rodríguez-Martínez, Ana; Cortés-Pascual, Alejandra; Quilez-Robres, Alberto (Frontiers in Education, 2021)
After analyzing the scientific literature referring to guiding actions developed in secondary education, there is an appreciable lack of research on process efficiency performed by teachers. This study explores the practice of tutoring, which in Spain is coordinated by counselors but the responsibility of teachers. An ad hoc semistructured questionnaire was designed, validated and applied within the framework of a collaboration agreement between professional institutions of counselors and researchers. The questionnaire was answered by 102 counselors who are heads of guidance departments because the insight of counseling experts was desired. The quantitative and qualitative data analyses indicated correlations between the profile of the counselors and the performance of tutoring, described the content and predominant intervention models and identified needs for improvement. A much more intensive and direct intervention by counselors is necessary in a system in which teachers are not trained enough and time dedicated to tutorial action is deficient. Notably, counselors coordinate and supervise tutoring, but they feel overwhelmed by the lack of concrete norms and their workload.